Missions as the theology of the church : an argument from Malawi - Fiedler, Klaus (Oxford [England] : Mzuni Press is represented outside Africa by African Books Collective., 2015)
The Christian faith is comprehensive and diverse, so the question, what the centre is, can be asked. Different answers have been given, to which this book adds another. The venture of the Christian faith is missions, following Kenneth Scott Latourette's thesis that the Holy Spirit moves forward the history of the church by bringing in ever new revivals, which produce ever new organisations. Therefore missions are not the children of the churches, but of the revivals, and Africa was not evangalised by the European and American churches, but by the Europeans and American mission societies.
The centre of all theology -- My background -- My presuppositions -- The first 1600 years -- The reformations -- Pietists, Puritans and orthodox theologians -- The Enlightenment -- The Great Awakening -- The Restorationist interlude -- The holiness revival (Second Evangelical Awakening) and the faith missions -- And then came the Pentecostals -- A new evangelical beginning -- And then the charismatics -- Edinburgh 1910/2010 -- Missions as the theology of the church and predestination -- The position of women in the kingdom of God -- Missions as theology of the church and Christian unity -- What about "wholistic mission?" -- Migration and the unity of the church -- Keep the revival.
Includes bibliographical references (pages 56-60) and index.
Print version record.
Keywords: Christianity -- Africa; Missions -- Africa -- History; Africa -- Church history; RELIGION -- Christianity -- History; Christianity; Missions; Africa; Electronic books; Church history; History